Surface & deep approaches to evaluating teaching - Daniel D. Pratt (Adult Education Research Conference, 1996)
The evaluation of teaching in adult and higher education tends to focus on surface rather than deep aspects of teaching perpetuating the perception that teaching is not scholarly work. Deep aspects of teaching are explained and nine principles for evaluation of teaching are offered.